Perbandingan Keamanan Vaksin mRNA COVID-19 Pada Ibu Hamil Dengan Ibu Tidak Hamil: Sebuah Review Sistematik - Ahmad Sabili Rifa'i; Clarishella Melvina Deinera; Bambang Satrio Utomo; Nadya Angelina; Budi Utomo; Khusnatul Mawaddah Arief (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
COVID-19 disease has spread all over the world. Some become acute respiratory distress syndrome or a more severe form of the disease that leads to death. Most of the vaccine effectiveness data currently available relate to mRNA vaccines. Pregnant women with COVID-19 are known to have a high risk of being admitted to the ICU. The increase with preterm births is still being observed in cases of complications caused by COVID-19. This research is a systematic review that uses articles. Research sources come from literature obtained from the online database Pubmed (n = 27), Web of Science (n = 18), Springerlink (n = 104) , and Science Direct (n = 266). Article searches were performed using the keywords (